Faktor yang mempengaruhi retensi karyawan milenial pada saat pandemi Covid-19: Kasus pada sebuah perusahaan BUMN di Indonesia - Eko Supriyadi; Dian Prasetya Ningrum; Eka Dewi Kurniawatiningsih; Farhan Bilal; Rezha Pahleviando; Indria Handoko (Journal of Business & Banking, 2021)
Employee turnover is one of key factors that can affect a company expenses, such as the increased cost of hiring and training new employees. During Covid-19 pandemic, where companies are facing not only health crisis, but also economic and social crises, the issue of turnover rate becomes more critical. This paper attempts to examine factors that can influence employee retention during the Covid-19 pandemic. In particular, the research will focus on millennial employees in one state-owned company in Indonesia, that unlike other companies, it has a low turnover rate since before until during the pandemic. This study is exploratory in nature, using in-depth interviews and focus group discussions to 13 employees from different positions. This research aims to find out what factors that make the millennial employees chose to stay even when the company was in a difficult situation. The findings suggest both extrinsic and intrinsic factors that have influenced the employees to stay. Extrinsic utilitarians factors found were job security, compensation, work environment, promotion, training, limited opportunities to work in other company, and chances to own a house at a young age. Whereas intrinsic factors were job challenges, work-life balance, job satisfaction, recognition, as well as gratitude and pride. This research contributes to build a better understanding on how to retain millennial employees, particularly in the Covid-19 pandemic.